Distribution of Vitamin D Status in a Group from Syrian Society - Almelli, Talleh (Jordan Journal of Pharmaceutical Sciences, 2023)
Objective: The aim of this work is to study the serum levels of 25-hydroxyvitamin D3 in a sample of healthy Syrians in the city of Homs. Method: A cross-sectional study, including 690 ostensibly healthy participants, was conducted at the National Hospital of Homs. Serum levels of 25-hydroxyvitamin D3 were measured using chemiluminescent immunoassay. Results: The overall prevalence of vitamin D inadequacy (insufficiency, deficiency, and severe deficiency) in the study samples was 76.5%. Additionally, 49% of the samples had vitamin D deficiency, with 18.5% suffering from severe deficiency. Furthermore, levels of 25-hydroxyvitamin D3 in females were lower than in males (11.3±2.3 ng/ml versus 39.6±11.28 ng/ml, respectively, p < 0.0001). Veiled women had serum levels of vitamin D lower than non-veiled women, 11.3±2.5 ng/ml versus 25.5±3.2 ng/ml, respectively, p < 0.0001. Female gender and clothing style were identified as independent risk factors for vitamin D deficiency. Conclusion: The prevalence of vitamin D deficiency was very common in the study population, despite the sunny weather in Homs city most of the year. Further studies with larger groups, including other Syrian governorates, are needed to elucidate lifestyle and sociocultural behavior risk factors for vitamin D deficiency.